1989
DOI: 10.1073/pnas.86.21.8422
|View full text |Cite
|
Sign up to set email alerts
|

Detection and mapping of spliced RNA from a human hepatoma cell line transfected with the hepatitis B virus genome.

Abstract: HepG2 cells, known to support the replication and virion formation of hepatitis B virus (HBV), were transfected with a cosmid constructed to contain 12 tandem head-to-tail repeats of the HBV genome for effective HBV genome expression. We detected previously identified RNAs of 3.3, 2.3, and 2.0 kilobases (kb) that code for core antigen, large surface antigen, and middle/major surface antigen, respectively. We also detected four additional RNAs of 2.1, 1.7, 1.1, and 0.7 kb [the lengths exclude the poly(A) tail].… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 14 publications
0
44
0
1
Order By: Relevance
“…2). The 5= sites at nt 2447, 2471, and 2985 and the 3= site at nt 489 are highly conserved and were reported as pregenomic RNA splicing sites by several investigators (19,33). Spliced defective viral DNA was infrequently detected in samples with a viral load of Ͻ10 4 IU/ml (12%) but was detected in 100% of samples with a viral load above 10 4 IU/ml (5 ϫ 10 4 copies/ ml).…”
Section: Discussionmentioning
confidence: 99%
“…2). The 5= sites at nt 2447, 2471, and 2985 and the 3= site at nt 489 are highly conserved and were reported as pregenomic RNA splicing sites by several investigators (19,33). Spliced defective viral DNA was infrequently detected in samples with a viral load of Ͻ10 4 IU/ml (12%) but was detected in 100% of samples with a viral load above 10 4 IU/ml (5 ϫ 10 4 copies/ ml).…”
Section: Discussionmentioning
confidence: 99%
“…; the 2.4 kb R N A was detected as a single 660 nt band, whereas the 2.0 kb RNA was separated into three discrete bands of 280,250 and 245 nts (Fig. 2) because of the heterogeneity of its 5' end, as described previously (Saito et al, 1986;Suzuki et al, 1989) and shown in Fig. 1 (b).…”
Section: Detection Of Hbsag Rnas In a Human Hepatoma Cell Line Infectmentioning
confidence: 95%
“…In the past few years several systems for propagating HBV in vitro in human cells have been reported (Sureau et al, 1986;Chang et al, 1987;Tsurimoto et al, 1987;Yaginuma et al, 1987;Sells et aL, 1988;Ochiya et al, 1989); in these systems pre-S2 and S RNAs (2.0 kb) are expressed abundantly, and pre-S1 (2.4 kb) RNA is expressed poorly. Suzuki et al (1989) reported abundant pre-S2 and S RNA (48.8 ~ of the total HBV RNA), and low pre-S1 RNA (7.1~ of the total HBV RNA) expression in human hepatoma cells (HepG2) transiently transfected with cloned HBV DNA.…”
Section: Introductionmentioning
confidence: 99%
“…S1 mapping. The procedure of S 1 nuclease protection mapping was described previously Suzuki et al, 1989). Briefly, 0.1 mg of total cytoplasmic RNA was hybridized at 53 °C with 0.2 lag of zzP-labelled probe DNA digested with nuclease S1 (500 units/ml; Boehringer Mannheim).…”
Section: Methodsmentioning
confidence: 99%